Bolton tooth size ratio among qatari population sample: An odontometric study - Hayder A Hashim; Najah AL-Sayed; Hashim AL-Hussain (Journal of Orthodontic Science, 2017)
Objectives: To establish the overall and anterior Bolton ratio among a sample of Qatari population and to investigate whether there is a difference between males and females, as well as to compare the result obtained by Bolton. Materials and Methods: The current study consisted of 100 orthodontic study participants (50 males and 50 females) with different malocclusions and age ranging between 15 and 20 years. An electronic digital caliper was used to measure the mesiodistal tooth width of all maxillary and mandibular permanent teeth except second and third molars. The Student′s t-test was used to compare tooth-size ratios between males and females and between the results of the present study and Bolton′s result. Results: The anterior and overall ratio in Qatari individuals were 78.6 ± 3.4 and 91.8 ± 3.1, respectively. The tooth size ratios were slightly greater in males than that in females, however, the differences were not statistically significant (P > 0.05). There were no significant differences in the overall ratio between Qatari individuals and Bolton′s results (P > 0.05), whereas statistical significant differences were observed in anterior ratio (P = 0.007). Conclusions: Within the limitation of the limitations of the present study, definite conclusion was difficult to establish. Thus, a further study with a large sample in each malocclusion group is required.